Nexus of violence and employment discrimination against women with disabilities in India – a scoping review - S.L. Ashalatha; Satish Kumar; K. Navin Kumar (Cogent Social Sciences, 2023)
The concept of violence has been considered a potential barrier to the inclusion of women with disabilities (WWD) and has raised interest in human resource management literature. However, existing studies have discussed the individual concepts of discrimination, inclusion, and violence against women with disabilities and studies with an apparent link examining the relationship between violence and employment discrimination (ED) have not been established by empirical research, and a confirmatory study is called for. The literature on the concepts of, violence and ED against WWD linkages is rarely established. As evidentially, few interventional studies have been conducted, leading us to follow a scoping review with the PCC model of PRISMA guidelines to carry out this study. This review article focuses on the causal relationship between violence and ED against WWD to provide an understanding of the existing literature, thereby identifying new research avenues for future research. Specifically, this scoping review identifies the nexus between antecedent violence against WWD and ED experiences, and provides insights that provide a comprehensive map connecting their linkages.